Business Sustainability Through Environmental and Operational Management in Five Star Hotels in Amman, Jordan - Haitham Abdelrazaq; Taghreed Aljaffal; Pheroza Daruwalla; Karina Wardle (STIE Malangkucecwara, 2021)
This paper aims to investigate sustainable environmental performance in five-star hotels in Amman, Jordan. The primary objective of the study is to determine the impact of business and operational practices of five-star hotels in Amman. The research focuses on five operational departments, including maintenance and security (MS), food and beverage (F&B), kitchens (K), purchasing (P), and housekeeping (H). This study adopted a qualitative method, using semi-structured interviews as the primary source for collecting extensive data. Moreover, the study employed quantitative instruments in data collection using a survey instrument and non-participatory observation as triangulation to the qualitative method. The study involved respondents from 13 fivestar hotels in Amman, Jordan. This paper examines the impact of operational business practices on environmental sustainability in five-star hotel properties in Amman. It suggests ways in which sustainable practices can contribute positively towards allowing hotels to achieve better performance towards the environment. The findings showed that all five-star hotels applied different sustainable practices in their daily operations to achieve sustainable environmental performance. Most of the respondents from the five operational departments acknowledged that suitable use of water and energy savings were the preferred choices that aided sustainability practices in the hotel properties